3(x-3)+4=4(x+7)+x

Simple and best practice solution for 3(x-3)+4=4(x+7)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)+4=4(x+7)+x equation:



3(x-3)+4=4(x+7)+x
We move all terms to the left:
3(x-3)+4-(4(x+7)+x)=0
We multiply parentheses
3x-(4(x+7)+x)-9+4=0
We calculate terms in parentheses: -(4(x+7)+x), so:
4(x+7)+x
We add all the numbers together, and all the variables
x+4(x+7)
We multiply parentheses
x+4x+28
We add all the numbers together, and all the variables
5x+28
Back to the equation:
-(5x+28)
We add all the numbers together, and all the variables
3x-(5x+28)-5=0
We get rid of parentheses
3x-5x-28-5=0
We add all the numbers together, and all the variables
-2x-33=0
We move all terms containing x to the left, all other terms to the right
-2x=33
x=33/-2
x=-16+1/2

You can always share this solution

See similar equations:

| z^2=10 | | 26-64=f | | 6x+2+6x=110 | | 3x/5/2=2 | | x^2+4x=120 | | X+X+10+(x+20)=360° | | 6-7v=-6v-3 | | X+X+10+(x+20)=360 | | -2-9f=5+9-7f | | 3=2x+3x+3 | | v+17?11=65 | | 1.69+2.1k=4.9k-9.38-4K | | X2+6x+30=0 | | -7z-10=10+3z | | -r+10=9r-10 | | 9.78+3.5u=-9.11+0.6u-0.25 | | 2x-(3x-8)=2 | | 8x^2-30x+45=0 | | 8x(2-30x+45=0 | | 7(6x=54) | | 8h+1=10+9h | | Q=1/2p+3 | | 7c+2+10c=-10c+2 | | 2x/2.8=8.2 | | 2t+10=4t-8 | | -10y+9=-7y-5y+9 | | -m+3=m-7 | | 3x+12=3x+25 | | 4x^-3+1=0 | | 6.4g+4=3.4g+10 | | -10d-1+3D=-d-1 | | 2.8/x=35 |

Equations solver categories